Advancing understanding of the linkages between local land policy interventions and the responsiveness of housing supply : Intervention mechanisms in the Finnish context - Lönnroth, Tea (Elsevier, 2025)
Land policy interventions are important ways for municipalities to implement their spatial development objectives. Such interventions may, however, generate both intended and unintended effects to housing supply and its responsiveness. It is therefore essential to better understand how and through what kind of mechanisms local land policy interventions can influence the quantity of housing supply. This paper addresses these questions. First, we develop a conceptual classification of so-called intervention mechanisms that describes the linkages between local land policy interventions and the quantity and responsiveness of housing supply. The intervention mechanisms build on a review of the urban economics literature and are further developed empirically using extensive expert interview data on local land policy interventions and practices in 30 Finnish municipalities. Based on the understanding that such intervention primarily influences housing supply through either direct or indirect costs on development, we conceptualize seven intervention mechanisms in the Finnish land policy context. Second, we demonstrate the variation in the application of land policy interventions that contribute to the (in)responsiveness of housing supply at the municipal level. Our findings highlight significant variation in the application of such interventions, potentially leading to different outcomes in housing supply restrictiveness. The findings contribute to a deeper understanding of the mechanisms by which land policy interventions operate to affect the (in)responsiveness of housing supply.